Understanding The Performance Measurement Of Data Analytics-Based Business Intelligence Technology In Financial Market Of Jordan - Mohammad Ali, Alokaily Aws Moufaq (2023)
The purpose of this thesis is to help fill this research gap and provide a measurement model of business intelligence technology benefits in listed firms Jordan's financial market.